The triad indole-3-acetic acid ethyl ester/esterase/horseradish peroxidase as a new cytotoxic prodrug/enzyme combination - Pereira, Débora Helena [UNESP]; Kitagawa, Rodrigo Rezende [UNESP]; Raddi, Maria Stella Gonçalves [UNESP]; Fonseca, Luiz Marcos da [UNESP]; Ximenes, Valdecir Farias [UNESP] (My University, 2010)
The antibody-directed enzyme prodrug therapy (ADEPT) is a means of restricting the action of toxic drugs to the tumor site. The enzyme/prodrug pair horseradish peroxidase (HRP)/indole-3-acetic acid (IAA) has been studied as a combination with potential application in ADEPT strategies. In this combination, the non-toxic plant hormone IAA is activated to cytotoxic species by the catalytic action of HRP. Objective: We studied the use of the ethyl ester of IAA as a new prodrug that could be activated by two enzymes, HRP and esterase. Methods: The oxidation of IAA and its ethyl ester, catalyzed by HRP, was monitored by the consumption of dioxygen and liquid chromatography. The cytotoxicity of IAA and its ethyl ester in combination with HRP and esterase was assessed using the lineage McCoy cells through the trypan blue and neutral red assays. Results: We found that HRP was not able to catalyze the oxidation of IAA-ethyl ester in the absence of an additional esterase. Hence, the potential cytotoxicity of the IAA-ethyl ester could be controlled by sequential treatment with esterase, to liberate the carboxyl group, and HRP, for oxidation and generation of cytotoxic species. We present evidence for the potential application of the combination IAA-ethyl ester/esterase/horseradish peroxidase as a new ADEPT, GDEPT or related strategy. Conclusions: We suggest that this technique could provide more selectivity in the generation of cytotoxic drugs at tumor sites.
Keywords: Indole-3-acetic acid synthase; Indole-3-acetic acid ethyl ester; Horseradish peroxidase; Esterases